2008
DOI: 10.3742/opem.2008.8.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin, a flavonoid antioxidant, protects streptozotocin-induced lipid peroxidation and β-Cell damage in rat pancreas

Abstract: SUMMARYThe present study is aimed at finding the influence of silymarin (a flavonoid) (25 mg/kg & 50 mg/kg) in streptozotocin (STZ)-induced diabetic rats. Type 2 diabetes was induced by single intraperitoneal injection of STZ (100 mg/kg) to 3 days old rat pups. Silymarin was administered for 15 days after the animals were confirmed diabetic (75 days after STZ injection). Blood glucose, glycosylated hemoglobin (HbA levels, which were elevated by STZ, were lowered to physiological levels by the administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…Silymarin, due to its antioxidant action has been found to be protective in alloxan induced diabetes (Soto et al, 1998, Soto et al, 2003 and anthracycline induced toxicity (Chlopeikova et al, 2004). Recently we have demonstrated that silymarin provides protection against STZ-induced lipid peroxidation and β cell damage in rat pancreas possibly by inhibiting lipid peroxidation and scavenging the free radicals (Sharma et al, 2008). These findings support the notion that possibly due to its antioxidant and membrane stabilizing properties silymarin is known to protect different organs and cells.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Silymarin, due to its antioxidant action has been found to be protective in alloxan induced diabetes (Soto et al, 1998, Soto et al, 2003 and anthracycline induced toxicity (Chlopeikova et al, 2004). Recently we have demonstrated that silymarin provides protection against STZ-induced lipid peroxidation and β cell damage in rat pancreas possibly by inhibiting lipid peroxidation and scavenging the free radicals (Sharma et al, 2008). These findings support the notion that possibly due to its antioxidant and membrane stabilizing properties silymarin is known to protect different organs and cells.…”
Section: Introductionsupporting
confidence: 78%
“…In our previous study we have shown that silymarin protects STZ-induced lipid peroxidation and β-cell damage in rat pancreas (Sharma et al, 2008). The reduction in lipoperoxidative damage by silymarin resulted in a significant decrease in blood glucose levels.…”
Section: Discussionmentioning
confidence: 89%
“…Moringa oleifera aqueous extract and polyphenolic compounds (Phenolic acids, hydroxycinnamic acids, hydroxycinnamic esters and flavonoids: silymarin, quercetin, apigenin, apigetrin) can exert antioxidant action on hepatocytes and pancreatic cells by scavenging free radicals, decreasing oxidative stress by reactive oxygen species (ROS). Alteration of the cellular antioxidant defense system occurs by increasing the activity of antioxidant enzymes (SOD, CAT, GST, GSHPx) and decreasing lipid peroxidation by reducing levels of (LPO, MDA, NO), resulting in β-cell protection of the pancreas against oxidative stress and decreasing the hyperglycemia generated by ROS (Ndong et al 2007;Jaiswal et al 2009Jaiswal et al , 2013Coskun et al 2005;Sharma et al 2008;Wang et al 2017;Zhang et al 2020).…”
Section: Resultsmentioning
confidence: 99%